Quasi-lumped bandpass filter with sharp transition edge and wide stopband rejection - Huang, H.-H; Chen, C.-H; Horng, T.-S (Electronics letters, 2013)
Presented is a highly miniaturised bandpass filter (BPF) with superior passband selectivity and high rejection over a wide stopband for 2.4 GHz WLAN applications. The proposed third-order coupled resonator design with a cross-coupled path provides an attenuation pole that is very close to the passband. Properly setting the fractional bandwidth and the resonator Q factor yields a sharp transition edge to suppress a 2.1 GHz WCDMA signal. Furthermore, the use of quasi-lumped LC resonators reduces the area of the BPF and generates multiple transmission zeros to enhance the desired stopband rejection.